2017
DOI: 10.5194/gmd-2017-65
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a more detailed representation of high-latitude vegetation in the global land surface model ORCHIDEE (ORC-HL-VEGv1.0)

Abstract: Abstract. To improve the simulation of vegetation-climate feedbacks in the high latitudes, three new circumpolar Plant Functional Types (PFTs) were added in the ORCHIDEE land surface model, namely non-vascular plants (NVPs) representing bryophytes and lichens, arctic shrubs, and arctic C3 grasses. Non-vascular plants are assigned no stomatal conductance, very shallow roots, and can desiccate during dry episodes and become active again during wet periods, which gives them a larger phenological plasticity compar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 52 publications
(86 reference statements)
1
30
0
Order By: Relevance
“…ORCHIDEE was first described in Krinner et al (), with the vegetation dynamics module directly introduced from the Lund‐Potsdam‐Jena model (Sitch et al, ). The version of ORCHIDEE used in this study (ORC‐HL‐VEGv1.0, Druel et al, ) includes key processes relevant for high latitudes: (i) a soil‐freezing scheme and its effect on root water availability and soil thermodynamics in order to represent permafrost (Gouttevin et al, ), (ii) an improved snow scheme describing the snow pack with three explicit snow layers (Wang et al, ) based on the ISBA‐ES LSM (Boone, ), and (iii) nonvascular plants (bryophytes and lichens, referred as moss in this article) and shrubs as two new plant functional types (PFTs) compared to the original version of ORCHIDEE, with specific equations and parameters (Table S1). Using a prescribed constant spatial distribution of the PFTs from a satellite land cover map, Druel et al () analyzed the impact of including these new PFTs on the net and gross carbon fluxes and the surface energy budgets over the boreal and Arctic zone.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…ORCHIDEE was first described in Krinner et al (), with the vegetation dynamics module directly introduced from the Lund‐Potsdam‐Jena model (Sitch et al, ). The version of ORCHIDEE used in this study (ORC‐HL‐VEGv1.0, Druel et al, ) includes key processes relevant for high latitudes: (i) a soil‐freezing scheme and its effect on root water availability and soil thermodynamics in order to represent permafrost (Gouttevin et al, ), (ii) an improved snow scheme describing the snow pack with three explicit snow layers (Wang et al, ) based on the ISBA‐ES LSM (Boone, ), and (iii) nonvascular plants (bryophytes and lichens, referred as moss in this article) and shrubs as two new plant functional types (PFTs) compared to the original version of ORCHIDEE, with specific equations and parameters (Table S1). Using a prescribed constant spatial distribution of the PFTs from a satellite land cover map, Druel et al () analyzed the impact of including these new PFTs on the net and gross carbon fluxes and the surface energy budgets over the boreal and Arctic zone.…”
Section: Methodsmentioning
confidence: 99%
“…The Rubisco‐limited carboxylation rate is given by the parameter Vc max(25) at 25 °C and the electron transport limited rate Vj max is assumed to be proportional to Vc max . The formulation of Vc max depends upon temperature (Yin & Struik, ), with an acclimation to seasonal temperature conditions through the monthly mean temperature as detailed in Druel et al (). Boreal vegetation has a lower Vc max(25) than standard PFTs (Table S1) and thus lower potential productivity in optimal conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While a previous study showed that the abundance of Picea decreases with latitude in the Tundra region and is coupled with the occurrence of dwarf shrubs in the Ericaceae and herbs (Gajewski et al, 1993), such species were not parametrized in the current version of LPJ-LMfire, due to a lack of information on their physiological and biogeographical preferences. Future research could incorporate recently developed parameterizations for 20 boreal shrubs and non-vascular plants into LPJ-LMfire (Druel, 2017;Druel et al, 2017).…”
Section: Uncertainties and Future Perspectivesmentioning
confidence: 99%